THE IMPORTANCE OF SECURITY AND CONSUMER TRUST ASPECTS IN ESTABLISHING CUSTOMER SATISFACTION IN TRANSACTIONS THROUGH E-COMMERCE - Mira Permata Sari; Rahadi Pratomo Singgih (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
This research is also aimed at answering the question of how consumer trust and security drive consumer satisfaction on E-Commerce and what efforts are being made to increase consumer security and trust in shopping online. This is qualitative research with a case study approach. Data collection was carried out by in-depth interviews. The interview technique in this research was carried out using a semi-structured method. In this research, researchers interviewed informants, namely consumers of Shopee, Tokopedia, and Lazada since they are the top three e-marketplace in Indonesia with the most visitors. Thus, source triangulation is applied in this research, namely by exploring data and information from consumers of different e-marketplaces. The result of this research shows that security and trust with indicators of benevolence, abilities, integrity, and willingness to depend is needed in establishing a customer satisfaction relationship between e-commerce and consumers, and especially in making transactions through e-commerce.